'We know it works. . .': The Troubled Families Programme and the pre-determined boundary judgements of decontextualised policy evaluation. (November 2020) - Silver, Daniel; Crossley, Stephen
This article draws on the Troubled Families Programme (TFP) to highlight the ways in which particular contexts – such as socioeconomic and symbolic structures – are neglected in forms of evaluation with an establishment orientation. The article problematises two key aspects of decontextualised evaluation: firstly, the privileging of pre-determined relations of cause and effect; and secondly, the unproblematized framing of policy problems. More contextualised forms of evaluation are presented as a way to open up boundaries of investigation. Lastly, it is argued that an anti-naturalist foundation for evaluation can broaden the scope of learning beyond the original framing of a policy.